Do dual-mobility cups cemented into porous tantalum shells reduce the risk of dislocation after revision surgery?: A retrospective cohort study on 184 patients. (4th March 2018) - Brüggemann, Anders; Mallmin, Hans; Hailer, Nils P
Abstract : Background and purpose — Dual-mobility cups (DMCs) reduce the risk of dislocation and porous tantalum (TM) shells show favorable osseointegration after acetabular revision surgery, yet the combination of these implants has not been studied. We hypothesized that (1) cementing a DMC into a TM shell decreases the risk of dislocation; (2) DMCs cemented into TM shells are not at greater risk of re-revision; (3) liberation of tantalum ions is marginal after use of this combined technique. Patients and methods — We investigated the outcome in 184 hips (184 patients) after acetabular revision surgery with TM shells, fitted either with DMCs (n = 69), or with standard polyethylene (PE) liners (n = 115). Chart follow-up was complete for all patients, and the occurrence of dislocations and re-revisions was recorded. 20 were deceased, 50 were unable to attend follow-up, leaving 114 for assessment of hip function after 4.9 (0.5–8.9) years, radiographs were obtained in 99, and tantalum concentrations in 84 patients. Results — 1 patient with a DMC had a dislocation, whereas 14 patients with PE liners experienced at least 1 dislocation. 11 of 15 re-revisions in the PE group were necessitated by dislocations, whereas none of the 2 re-revisions in the DMC group was performed for this reason. Hence, dislocation-free survival after 4 years was 99% (95% CI 96–100) in the DMC group, whereas it was 88% (CI 82–94, p = 0.01) in the PE group. We found no radiographic signs of implant failure in any patient. Mean tantalum concentrations were 0.1 µl/L (CI 0.05–0.2) in the DMC group and 0.1 µg/L (CI 0.05–0.2) in the PE group. Interpretation — Cementing DMCs into TM shells reduces the risk of dislocation after acetabular revision surgery without jeopardizing overall cup survival, and without enhancing tantalum release.